Other-correction and epistemic imbalances in teacher–student interactions - Li, Min; Yue, Yang (East Asian Pragmatics, 2024)
Other-correction is a ubiquitous phenomenon in language, and has been extensively studied in conversation analysis and pragmatics. Nevertheless, the conditions of its occurrence still remain unclear. Based on Heritage’s theory of epistemics, the study unveils four distinct epistemic interaction patterns in which other-correction takes place, and endeavours to elucidate their associations with trouble sources, correction strategies, and correction positions. Empirical findings indicate that different epistemic interaction patterns of other-correction exhibit no discernible link with trouble sources, but manifest a statistically significant correlation with correction strategies and correction positions.